A DISCOURSE ANALYSIS OF RHETORICAL STYLE IN RESEARCH ARTICLE INTRODUCTION IN LAW STUDIES WRITTEN BY INTERNATIONAL AUTHORS - Ejontomi Afrizon; Safnil Arsyad; Zahrida . (Journal of English Education and Teaching, 2018)
This research is aimed at finding the most dominant move, step and the most common pattern of rhetorical style in Research Article Introduction in Law Studies Written By International Authors. The documentation technique  and checklist were  used  in this research. Fifteen English RA introductions by International authors were analyzed by using disourse analysis technique, using quantitative as well as qualitative method and following Swales’s CARS Model (1990). The results show that the authors dominantly use Move 1 (Establishing a territory) and Step 2 of Move 1 (Making Topic Generalisation). The fifteen articles mostly have the same model in leading to understanding to the article introduction. In addition, International authors of English RAs in Law Study prefer describing the phenomena and found the problem based on it to describing the previous research. The most common pattern is Complete Pattern. The articles which belong to Complete Pattern have three moves. While the one which has two moves belong to Semi complete and the one which has one move only belong to incomplete pattern. In conclusion, the articles in the three journals are categorized into appropriate articles in term of discourse structure.